A robust model-based control for uncertain systems - Hamamci, SE; Ucar, A (Sage Publications Ltd, 2002)
A new robust control strategy coefficient diagram method (CDM), which is an algebraic approach applied to a polynomial loop in the parameter space, is studied in this paper. Here, a model-based CDM is developed and proposed for uncertain systems. A special diagram called a coefficient diagram, which is used as a vehicle to carry the necessary information and as the criteria of good performance, is designed and modified accordingly. The performance of this novel controller is illustrated through several examples, and numerical results are provided.
Keywords: coefficient diagram method (CDM); model-based control; robust control; stability index; uncertain system